Mountain hay meadows: assessing the loss of surfaces and ecosystem services in Iberian areas - García Manteca, Pilar (2019)
Hay meadows, agro-ecosystems established and maintained by human secular actions of extensive management, are disappearing all over Europe, especially in mountain areas where they represent key High Nature Value Farming systems for biodiversity and ecosystem services. In recent times, also mesophile hay meadows in South-West Europe, a European priority habitat registering a poor conservation status, have lost significant part of their area. This disappearance is due to abandonment, intensification or urbanisation, driven by changes in land management and rural socio-demographic decline. This study is aimed at assessing the loss of mountain hay meadows in the North of the Iberian Peninsula and its consequences for ecosystem services, focusing on selected pilot areas currently protected as Natura 2000 sites. A diachronic analysis of these habitats was carried out through detailed land use mapping for three different periods, from the 1960s to the present, representing areas covered by hay meadows over time. Once identified, land use changes during the time under consideration have been quantified and analysed, as well as the drivers responsible for those changes. The conceptual framework of the Millenium Ecosystem Assessment was then applied to identify and discuss the most relevant consequences of change on ecosystem services. Results showed that, over the last 60 years, some study areas have lost up to 74% of hay meadows progressively, although at a higher rate in the latest years. A relationship between abandonment and slope and distance to inhabited areas has been also observed. Findings suggest that the observed abandonment process may lead to a loss of biodiversity (domesticated species) and impacts in the supply of strategic ecosystem services such as genetic resources, safe and healthy food products, traditional knowledge or fire risk protection. Interactions between hay meadows loss, ecosystem services, demographic processes and agricultural structural changes are finally discussed.